Biological Otherness: Multispecies Agencies and Elastic Temporalities in Exhibition Practices - Ramirez-Figueroa C; Lin P-Y; Nevin A (MDPI AG, 2026)
This contribution examines how contemporary exhibition practices engage with biological otherness through the interplay of material, technological mediation and curatorial practice. It explores how organisms and materials often considered marginal, such as viruses, microbial life, dust, and ash, can operate as co-authors in exhibition-making, unsettling hierarchies and binary frameworks that privilege human perception and control. Biological matter becomes a medium for thinking with and through nonhuman perspectives, revealing entangled temporalities, rhythms, and ecologies that exceed conventional scales of perception. Through three case studies: Living Ashes II, Studies of Interbeing—Trance 1:1, and The Materialised Temporality of Dust, the paper interrogates how decomposition, infection, and microscopic life are translated into relational, multisensory experiences. In Living Ashes II, protocells and ash are staged as agents of emergent vitality; in Studies of Interbeing—Trance 1:1, SARS-CoV-2 is re-materialised through textile and performative practices, fostering intimacy and affective encounter; and in The Materialised Temporality of Dust, immersive VR and spatial sound render microbial and dust temporalities perceptible within architectural space. Across these projects, digital technologies function not as neutral instruments but as active mediators, shaping the conditions under which nonhuman agency, vibrancy, and unpredictability are apprehended. Collectively, these works demonstrate that exhibitions can operate as relational laboratories in which biological otherness is co-produced, negotiated and experienced. They foreground an ethic of care and attunement, emphasising the multispecies, temporal, and technological entanglements that redefine what it means to exhibit living and non-living matter in the digital age.
Keywords: relational practices; biological otherness; multispecies exhibition; elastic temporalities